A Case of Rituximab-Induced Necrotizing Fasciitis and a Review of the Literature. (26th September 2017) - Abdulkareem, Abdullateef; D'Souza, Ryan S.; Shogbesan, Oluwaseun; Donato, Anthony
Abstract : Necrotizing fasciitis is a fulminant soft tissue infection characterized by rapid progression and high mortality. Rituximab is a generally well-tolerated immunosuppresive medication used for B-cell malignancies and some rheumatological disorders. We report a case of a 69-year-old male with chronic lymphocytic leukemia who suffered necrotizing fasciitis of his left lower extremity secondary to Clostridium septicum 7 weeks after treatment with rituximab. Despite immediate intravenous antimicrobial therapy and emergent fasciotomy with extensive debridement, his hospital course was complicated by septic shock and he required an above-the-knee amputation. Physicians need to be aware of the possibility of necrotizing fasciitis in patients presenting with skin infections after rituximab therapy.